Microsatellite marker-based genetic diversity of tropical-adapted shrunken-2 maize inbred lines and its relationship with normal endosperm inbred lines of known heterotic classification (2020)
Knowledge of the genetic diversity and relationships among maize inbred lines can facilitate germplasm management and plant breeding programmes. The study investigated the level of genetic diversity among S6 lines developed from a tropical-adapted shrunken-2 (sh-2) maize population and their relationship with normal endosperm tropical inbred lines of known heterotic groups. Ninetyone sh-2 maize inbred lines (UI1-UI91) developed in the University of Ibadan super-sweet Maize Breeding Programme were genotyped at 30 simple sequence repeat (SSR) loci, alongside five normal endosperm maize inbred lines viz. TZi3, TZi4, TZi10, TZi12 and TZi15, four of which belong to two heterotic groups. Twenty-three SSR markers were polymorphic and detected a total of 61 alleles, with a range of 2–7 and an average of 2.65 alleles per locus. The polymorphic information content ranged from 0.12 in bnlg1937 to 0.77 in phi126, with an average of 0.36. The gene diversity (He) averaged 0.43. Cluster analysis resulted in five groups consisting of 16, 36, 17, 23 and 3 inbred lines, with one sh-2 line ungrouped. TZi 12 and TZi 15, both of which are of the same heterotic group, clustered with TZi 3 of another heterotic group. Considerable genetic diversity exists among the 96 inbred lines. Only two of the five normal endosperm lines shared clusters with the sh-2 lines. The clustering of the normal endosperm inbred lines is not related to their established heterotic patterns. Inbred lines in two clusters offer the possibility of guiding the exploitation of heterosis among the sh-2 lines.